Design of Structural Parameters of Centrifugal Elevator Overspeed Governors - Yunpu Song; Cheng Chen (Institute of Advanced Engineering and Science, 2014)
As an important part of overs-peed and fail-safe protection for elevators, the centrifugal elevator overspeed governor is a device for limiting overspeed of elevator cars. This paper researches on the impact of the spring stiffness of the centrifugal block, which plays a key role in the performance of this overspeed governor, on the operation of the over-speed governor. By setting up a mathematical model and further carrying out simulation analysis, this paper researches on the influence of systematic parameters, such as the mass of centrifugal block, the turning radius of the centrifugal block, the amount of spring compression of the centrifugal block, on the spring stiffness of the centrifugal block, and obtains their specific influence relationship. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4839